Pakistan Federal Government : Public Financial Management and Accountability Assessment - Government of Pakistan; World Bank Group; U.K. Department for International Development; European Union; Asian Development Bank (World Bank, Washington, DC, 2017)
This document reports on a Public Financial Management and Accountability Assessment (PFMAA) for the Federal Government of Pakistan (GoP). Measured against the six core Public Financial Management (PFM) objectives examined by the assessment, the assessment indicates that there have been improvements in some areas in recent years, which have served to improve general public financial management. The last PEFAA for the Federal Government was published in June 2009. Overall, the maximum number of indicators remained unchanged. As PFM concerns the efficiency and effectiveness of the use of public resources, the interdependence of the components of the budget cycle means that weaknesses in one part can adversely affect other parts thereby constraining the achievement of better budgetary outcomes; conversely, improvements in one area which are not matched by corresponding changes in other areas can undermine the initial reforms. The strengths and weaknesses of Pakistan's public financial management system found in the assessment have an impact on the three measures of budget effectiveness-aggregate fiscal discipline, allocates efficiency and efficient service delivery. The GoP has a continuing agenda of PFM reform. Current programs are focused on areas of weaknesses in PFM administration that have been identified by the GoP and development partners. Pakistan's prospects for reform implementation should be regarded as positive considering the impact of the reform programs so far which have made visible contributions in improving budgeting, reporting and external audit. The PEFA framework focuses on operational performance of the key elements of the PFM system based on evidence rather than on the inputs that enable the PFM system to reach a certain level of performance. The PFMAA assesses the extent to which the PFM system is an enabling factor for achieving budgetary outcomes at the three levels of aggregate fiscal discipline, strategic allocation of resources and efficient service delivery.